2015
DOI: 10.5271/sjweh.3490
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of neurosensory disorders and reduced work ability to alternative frequency weightings of hand-transmitted vibration

Abstract: This is the first epidemiological study with a prospective cohort design that investigates the relationships of neurosensory disorders and reduced work ability to vibration exposure assessed by means of a set of alternative frequency weightings of hand-transmitted vibration (HTV). The study provides epidemiological support to the choice of appropriate frequency weightings of HTV by ISO standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…In a 3-year follow-up study of 249 hand-arm vibration exposed workers and 138 referents, the workers had a higher prevalence and cumulative incidence of neurosensory disorders in hands and a reduced work ability compared to the referents [29]. The intensity of the daily vibration exposure and the duration of exposure in years were significantly related to both neurosensory findings and work ability [29]. The vibration perception threshold was the most sensitive QST-parameter to diagnose adverse health neurosensory findings in a study of chain saw workers and stone cutters [30].…”
Section: Discussionmentioning
confidence: 99%
“…In a 3-year follow-up study of 249 hand-arm vibration exposed workers and 138 referents, the workers had a higher prevalence and cumulative incidence of neurosensory disorders in hands and a reduced work ability compared to the referents [29]. The intensity of the daily vibration exposure and the duration of exposure in years were significantly related to both neurosensory findings and work ability [29]. The vibration perception threshold was the most sensitive QST-parameter to diagnose adverse health neurosensory findings in a study of chain saw workers and stone cutters [30].…”
Section: Discussionmentioning
confidence: 99%
“…This being the case we needed to know the cut-off from normal of sensory perception using monofilaments in the fingers of asymptomatic non-vibration exposed male heavy manual workers and whether previously published normal data for the Purdue pegboard applied to heavy manual workers. Both questions were addressed by an expert re-analysing his previously published data on non-vibration-exposed maintenance workers as medians and interquartile ranges (Bovenzi et al 2015 ). This was done as normal limit values by age and hand.…”
Section: Methodsmentioning
confidence: 99%
“…Literature on factors that predict work ability based on longitudinal data that span 10 years or more is rather limited. Studies have found that working conditions, such as the psychosocial work environment (Feldt et al 2009) and physical work demands (von Bonsdorff et al 2011b), including hand-transmitted vibration (Bovenzi et al 2015), and individual factors such as musculoskeletal pain, depressive symptoms (Punakallio et al 2014) and mental work strain (von Bonsdorff et al 2011b), are related to an adverse development in work ability. Based on these previous findings, we designed this study.…”
Section: Introductionmentioning
confidence: 99%